Flake-shaped silicon negative electrode material, manufacturing method for the same, and applications for the same
The production of a flake silicon negative electrode material through a composite structure with graphene and carbon layers addresses volume changes in silicon anodes, enhancing efficiency and stability for lithium-ion batteries.
Patent Information
- Application Number
- JP2023151869
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2043-09-20
AI Technical Summary
Existing silicon anode materials for lithium-ion batteries face issues with large volume changes due to lithium ion insertion and desorption, leading to mechanical destruction, rapid capacity loss, and SEI layer degradation, with manufacturing methods being inefficient and lacking reproducibility.
A method involving the production of a flake silicon negative electrode material using calcium silicide at specific temperatures, followed by acid pickling, mixing with graphene oxide, and calcination with a cationic polymer to form a composite structure that suppresses volume expansion and enhances mechanical strength and conductivity.
The method produces a silicon anode material with improved efficiency, reproducibility, and stability, suitable for mass production, offering high specific capacity and long cycle life in lithium-ion batteries.
Smart Images

Figure 2025044350000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a flaky silicon negative electrode material, a manufacturing method thereof, and uses thereof, and more specifically, to a flaky silicon negative electrode material suitable as a negative electrode material for lithium ion secondary batteries, and a manufacturing method thereof. [Background technology]
[0002] Silicon (Si) has attracted attention as an anode material for lithium-ion secondary batteries because of its large specific capacity, low operating potential, and natural abundance. However, Si anodes have problems in that they undergo large volume changes due to the insertion and desorption of lithium (Li) ions, leading to accelerated decomposition and short cycle life. In addition, mechanical destruction during the alloying / dealloying process between Si and Li causes a rapid and irreversible capacity loss. Furthermore, the desorption of Li destroys the solid electrolyte interphase (SEI) layer on the Si surface, exposing the new Si surface to the electrolyte and forming an SEI layer, which causes the SEI layer to thicken with repeated charging and discharging.
[0003] In response to the problem of such a large volume change, the inventors of the present application have proposed an anode electrode material containing a composite having a silicon sheet, a graphene sheet sandwiching the silicon sheet, and a carbon material positioned between the silicon sheet and the graphene sheet, and a manufacturing method thereof (Patent Document 1). According to the manufacturing method of the anode electrode material described in Patent Document 1, it is possible to obtain an anode electrode material that suppresses volume expansion and enables high capacity. However, in the manufacturing method described in Patent Document 1, SiO x (x is 0≦x≦1) Since it takes a relatively long time (7 days in the embodiment) to produce the sheet, there is room for improvement in terms of efficiency.
[0004] In addition, Non-Patent Document 1 describes calcium silicide (CaSi 2) at specific temperature conditions (550℃, 650℃, 750℃) 2 It is described that a structure (L-Si / C) in which layers of silicon atoms and layers of carbon atoms overlap can be obtained by reacting the silicon atoms with the carbon atoms, and that the structure has good cycle characteristics and rate characteristics as an anode electrode material. However, according to a follow-up experiment by the present inventors, there is still room for further improvement in the manufacturing method, mainly from the viewpoint of reproducibility. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-166163 A [Non-patent literature]
[0006] [Non-Patent Document 1] Y. An et al., ACS Nano 2020, 14, 17574-17588. Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above, an object of the present invention is to provide a method for producing silicon anode materials with improved efficiency and reproducibility, which is more suitable for practical use. Another object of the present invention is to provide a silicon negative electrode material produced by the above-mentioned production method, and uses of the silicon negative electrode material. [Means for solving the problem]
[0008] The method for producing the flake silicon negative electrode material according to the present invention is to use calcium silicide (CaSi 2 ) at temperatures between 800℃ and 950℃. 2) to obtain an intermediate structure, pickling the intermediate structure with an acid pickling solution to obtain a silicon sheet, mixing the silicon sheet and the graphene oxide sheet in a dispersion medium to obtain a mixture, mixing the mixture with an aqueous solution of a cationic polymer to obtain a precursor, and calcining the precursor, thereby solving the above-mentioned problem. Obtaining the intermediate structure comprises: 2 Under temperature conditions of 860℃ to 940℃, 2 It may be reacted with. Obtaining the intermediate structure comprises: 2 Under temperature conditions of 875℃ to 925℃, 2 It may be reacted with. Obtaining the intermediate structure comprises: 2 CO 2 The reaction may be carried out for more than 5 hours and up to 15 hours. Obtaining the intermediate structure comprises: 2 In a reactor containing CO 2 By supplying CaSi at a flow rate in the range of 0.15 L / min to 0.3 L / min, 2 CO 2 It may be reacted with. The pickling solution may be an aqueous solution of an acid selected from the group consisting of sulfuric acid, hydrochloric acid and nitric acid. Obtaining the mixture may involve mixing the silicon sheet and the graphene oxide sheet in a mass ratio that satisfies a range of 65:35 to 75:25. The cationic polymer may be at least one selected from the group consisting of polyethyleneimine (PEI), polyvinylamine, polyallylamine, protamine, polylysine, polyornithine, polyarginine, chitosan, and polyvinyl alcohol. Calcining the precursor may be carried out at a temperature in the range of 600°C to 1000°C. Obtaining the mixture may involve mixing the silicon sheet and the graphene oxide sheet under pressure. Effect of the Invention
[0009] The method for producing the flake silicon anode material of the present invention is 2 A silicon sheet is produced by a gas phase reaction using a carbon source material, which is then mixed with the carbon source material and sintered. This method does not require skilled techniques or expensive equipment, is inexpensive and efficient, and has a low environmental impact, making it suitable for mass production. The flake silicon negative electrode material produced by the method of the present invention is also suitable as a negative electrode material for lithium ion secondary batteries. [Brief description of the drawings]
[0010] [Figure 1] A flow chart showing the manufacturing process of the flake silicon negative electrode material of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing a composite constituting the flake silicon negative electrode material of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a lithium-ion secondary battery of the present invention. [Figure 4] (a) and (b) are SEM images of the raw material CaSi2, and (c) and (d) are SEM images of the intermediate structure (Example 6). [Figure 5A] 1 shows SEM images of silicon sheets obtained using the intermediate structures of Examples 4 and 5. [Figure 5B] 1 shows SEM images of silicon sheets obtained using the intermediate structures of Examples 6 and 7. [Figure 6] (a) and (b) are SEM images of the silicon sheet of Example 6, and (c) and (d) are SEM images of the flake silicon negative electrode material of Example 6. [Figure 7] FIG. 1 shows an SEM image of the flake silicon negative electrode material of Example 6 and the results of element mapping analysis using the SEM image. [Figure 8] FIG. 1 shows XRD patterns of (a) raw CaSi2, (b) intermediate structure, (c) silicon sheet, and (d) flake silicon negative electrode material for Example 6. [Figure 9] FIG. 1 shows Raman spectra of (a) the silicon sheet of Example 6 and (b) the flake silicon negative electrode material of Example 6. [Figure 10]FIG. 1 shows XPS spectra of the silicon sheet of Example 6 (lower row) and the flake silicon negative electrode material of Example 6 (upper row). [Figure 11] FIG. 14 shows nitrogen adsorption / desorption isotherms of (a) the raw material CaSi2, (b) the flake silicon negative electrode material, and (c) the pore size distribution of the flake silicon negative electrode material in Example 6. [Figure 12] FIG. 1 shows the current-potential curve of the battery of Example 6. [Figure 13] FIG. 6 shows the charge / discharge profile of the battery in Example 6. [Figure 14] FIG. 1 shows the rate characteristics of the battery of Example 6 [Figure 15] Figure showing the Nyquist plot of the battery in Example 6 [Figure 16] FIG. 1 shows cycle characteristics of the battery of Example 6 [Figure 17] FIG. 1 shows current-potential curves obtained at different sweep rates for the battery of Example 6. [Figure 18] A graph showing the relationship between the logarithm of the peak current (unit: A) and the logarithm of the sweep rate (unit: mV / s) [Figure 19] FIG. 1 shows the ratio of capacitive and diffusion-controlled contributions in the Li absorption process obtained for the battery of Example 6 at different sweep rates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that like elements are given like reference numerals and their description will be omitted.
[0012] (Embodiment 1) In the first embodiment, a method for producing a flake silicon negative electrode material of the present invention will be described. FIG. 1 is a flow chart showing the manufacturing process of the flake silicon negative electrode material of the present invention.
[0013] Step S110: Calcium silicate (CaSi 2 ) at temperatures between 800℃ and 950℃. 2 ) to give the intermediate structure.
[0014] CaSi 2 is the raw material of the silicon sheet constituting the flake silicon anode material of the present invention. Among the silicides, CaSi 2 Since the silicon atoms have a wavy hexagonal structure and the Ca layer and the Si layer are laminated to form a plate-like structure (also called a flat plate structure), it can be suitably used as a raw material for silicon sheets.
[0015] In step S110, the temperature condition is set to be higher than 800°C. If the temperature condition is 800°C or lower, the silicon sheet obtained through step S120 described later may have non-negligible impurities mixed in (residual), which may impair the properties as a negative electrode material. In this context, the temperature condition is preferably 850°C or higher. In addition, in step S110, the temperature condition is set to be lower than 950°C. If the temperature condition is 950°C or higher, the silicon sheet obtained through step S120 described later may have nanosheets aggregate with each other, which may impair the properties as a negative electrode material. The temperature condition in step S110 is preferably in the range of 860°C or higher and 940°C or lower, and more preferably in the range of 875°C or higher and 925°C or lower.
[0016] The reaction in step S110 is typically 2 In a reactor (heating furnace) containing 2 In this embodiment, the reaction is carried out by supplying CO 2 The amount of CaSi supplied depends on the reaction scale (reactor shape, size, and 2 The reaction flow rate can be appropriately adjusted depending on the reaction scale (e.g., the amount of CaSi), and may be, for example, in the range of 0.15 L / min to 0.3 L / min. Similarly, the reaction time can be appropriately adjusted depending on the reaction scale, and may be, for example, in the range of more than 5 hours to 15 hours, and preferably, in the range of 7 hours to 13 hours. 2 and CO 2From the viewpoint of effectively and efficiently proceeding with the reaction, it is preferable to consider adjusting reaction conditions other than those mentioned above.
[0017] In step S110, CaSi 2 Ca layer (calcium atom) and CO 2 The reaction with calcium carbonate (CaCO 3 ) is generated between and / or around the Si layers, and CaCO 3 An intermediate structure is formed having a structure in which
[0018] Step S120: The intermediate structure obtained in step S110 is pickled using an acid pickling solution to obtain a silicon sheet.
[0019] In step S120, a known pickling solution (pickling liquid) can be used. In a preferred embodiment, the pickling solution is selected from the group consisting of sulfuric acid, hydrochloric acid, and nitric acid. In a typical embodiment, the intermediate structure is pickled with hydrochloric acid. By pickling the intermediate structure, CaCO 3 In addition, the raw material CaSi is removed by pickling. 2 Impurities and the like that may have been present in and / or may have been generated during step S110 are removed. As a result, a silicon sheet composed of several Si layers is obtained.
[0020] Step S130: The silicon sheet and the graphene oxide sheet obtained in step S120 are mixed in a dispersion medium to obtain a mixture.
[0021] The mixture obtained through step S130 may typically have a structure in which the silicon sheet is sandwiched between graphene oxide sheets. Hereinafter, this structure will be referred to as a silicon sheet / graphene oxide sheet sandwich.
[0022] Any graphene oxide sheet can be used as long as it can be reduced to a graphene sheet. The graphene oxide sheet may be obtained by producing graphite oxide from commercially available graphite powder by the Brodie method, the Staudenmaier method, the Hummers method, the modified Hummers method, or the like, and then peeling it off. Centrifugation or ultrasonic treatment may be used for the peeling. Exemplary conditions for the centrifugation include a rotation speed of 10,000 rpm to 35,000 rpm for 10 minutes to 60 minutes, and the centrifugation may be repeated until the pH reaches 7.
[0023] In step S130, the silicon sheet and the graphene oxide sheet are mixed preferably in a mass ratio of silicon sheet:graphene oxide sheet=65:35 to 75:25. Within this range, the production of the above-mentioned silicon sheet / graphene oxide sheet sandwich is promoted. The silicon sheet and the graphene oxide sheet are more preferably mixed in a mass ratio of silicon sheet:graphene oxide sheet=68:32 to 73:27.
[0024] In step S130, the dispersion medium may be water or an aqueous solution of an acid selected from the group consisting of sulfuric acid, hydrochloric acid, and nitric acid, which allows the silicon sheet and the graphene oxide sheet to be well dispersed, thereby obtaining a silicon sheet / graphene oxide sheet sandwich.
[0025] In step S130, the weight concentration of the mixture in the mixed solution is preferably in the range of 15 g / L to 20 g / L, inclusive, in which the silicon sheet and the graphene oxide sheet are well dispersed and a silicon sheet / graphene oxide sheet sandwich is obtained.
[0026] The mixing in step S130 may be performed under atmospheric pressure or under pressure, which can facilitate the production of a silicon sheet / graphene oxide sheet sandwich.
[0027] Step S140: The mixture obtained in step S130 is mixed with an aqueous solution of a cationic polymer to obtain a precursor.
[0028] In step S140, the silicon sheet / graphene oxide sheet sandwich may be aggregated in the mixed solution due to electrostatic interaction caused by mixing with the cationic polymer, and the cationic polymer may be positioned between the silicon sheet and the graphene oxide sheet and / or to cover (wrap) the silicon sheet / graphene oxide sheet sandwich. Such aggregates and / or coverings are the precursor. Hereinafter, the precursor is referred to as silicon sheet / graphene oxide sheet / cationic polymer.
[0029] The mixing in step S140 is preferably performed by adding the above-mentioned mixture (i.e., the silicon sheet / graphene oxide sheet sandwich) to an aqueous solution of a cationic polymer, which promotes packaging, coating, and encapsulating of the silicon sheet / graphene oxide sheet sandwich with the cationic polymer.
[0030] The cationic polymer is not particularly limited as long as it is water-soluble and cationic, but illustratively, at least one selected from the group consisting of polyethyleneimine (PEI), polyvinylamine, polyallylamine, protamine, polylysine, polyornithine, polyarginine, chitosan, and polyvinyl alcohol is selected. These are easily available, water-soluble, and cationic. Among these, polyethyleneimine (PEI), (aminoacetalized) polyvinyl alcohol, and chitosan are preferred because they promote the coating and encapsulation of the silicon sheet / graphene oxide sheet sandwich.
[0031] The concentration (wt%) of the cationic polymer in the aqueous solution of the cationic polymer is preferably in the range of 1.0 wt% or more and 3.0 wt% or less. This range promotes the coating and encapsulation of the silicon sheet / graphene oxide sheet sandwiched body with the cationic polymer. The concentration (wt%) of the cationic polymer is preferably in the range of 1.5 wt% or more and 2.5 wt% or less. This results in a silicon sheet / graphene oxide sheet / cationic polymer.
[0032] The mixture in step S140 may be the mixture filtered from the mixed liquid in step S130, or may be the unfiltered mixed liquid. In this case, the amount of the mixed liquid to be mixed with the aqueous solution of the cationic polymer is preferably in the range of 1 to 3 times the volume of the aqueous solution. In this range, the silicon sheet / graphene oxide sheet sandwich is more reliably coated / encapsulated by the cationic polymer, and a silicon sheet / graphene oxide sheet / cationic polymer is obtained.
[0033] Step S150: The precursor obtained in step S140 is calcined.
[0034] In step S150, the silicon sheet / graphene oxide sheet / cationic polymer is calcined, so that the graphene oxide in the graphene oxide sheet is reduced to a graphene nanosheet, and the cationic polymer is converted to a carbon material, thereby obtaining the flake silicon anode material of the present invention.
[0035] In step S150, the calcination is preferably performed at a temperature in the range of 600° C. to 1000° C. This range allows the graphene oxide to be reduced and the cationic polymer to be calcined. The calcination is more preferably performed at a temperature in the range of 700° C. to 900° C. This range promotes the reduction of the graphene oxide and converts the cationic polymer into a carbon material.
[0036] Calcination is preferably carried out in an inert gas atmosphere such as nitrogen, argon, helium, neon, xenon, etc., which facilitates calcination of the precursor materials.
[0037] The firing time is not particularly limited, but is illustratively performed for 30 minutes to 12 hours. If it is shorter than 30 minutes, firing may be insufficient. If it exceeds 12 hours, firing may not proceed any further and may be inefficient. The firing time is preferably 1 hour to 5 hours.
[0038] In one embodiment, prior to step S150, the mixture obtained in step S140 may be dried in a vacuum at a temperature in the range of 30° C. to 60° C. This promotes the firing in step S150.
[0039] (Embodiment 2) In the second embodiment, a flake silicon negative electrode material of the present invention will be described. The flake silicon negative electrode material of the present invention is suitably produced by the production method described in the first embodiment. FIG. 2 is a schematic diagram showing a composite constituting the flake silicon negative electrode material of the present invention.
[0040] The composite 200 constituting the flake silicon negative electrode material of the present invention has a silicon sheet 210, a graphene sheet 220 sandwiching the silicon sheet 210, and a carbon material 230 located between the silicon sheet 210 and the graphene sheet 220. Note that in FIG. 2, the graphene sheet 220 and the carbon material 230 are shown as distinguishable for ease of understanding, but in an actual composite, they may be an integral structure. That is, in one embodiment, the composite 200 has a silicon sheet 210 and a carbon-containing layer containing the graphene sheet 220 and the carbon material 230, and the carbon-containing layer sandwiches the silicon sheet 210. In other words, the composite 200 of this embodiment is a structure in which the silicon sheet 210 is covered or encapsulated by the carbon-containing layer. In the flake silicon negative electrode material of the present invention, the carbon-containing layer not only serves as a protective layer that protects the silicon sheet (Si layer) from unintended damage or destruction, but can also contribute to increasing the mechanical strength of the entire material and improving its electrical conductivity.
[0041] In the composite 200, the graphene sheets 220 sandwich the silicon sheet 210, so that when the composite 200 is used as a negative electrode material for a lithium ion secondary battery, the volume expansion of silicon due to the insertion and desorption of Li ions is suppressed, and the cycle characteristics can be improved. In addition, the silicon sheet 210 and the graphene sheet 220 are both densely aggregated because nanosheets having a thickness of atomic level to nanometer order are layered. As a result, a large specific capacity of silicon is achieved, so that the flake silicon negative electrode material of the present invention containing the composite 200 is advantageous for increasing the capacity of a lithium ion secondary battery. The silicon sheet is sandwiched between the graphene sheets having excellent flexibility, so that it can follow the volume change accompanying the absorption and release of Li ions. As a result, the composite 200 constituting the flake silicon negative electrode material does not break, enabling a long life of the lithium ion secondary battery.
[0042] The silicon sheet 210 is a laminate (aggregate) of silicon sheets in which silicon atoms are periodically arranged in the two-dimensional direction and have Si-Si bonds. In detail, the silicon sheet has six-membered Si rings periodically arranged in the two-dimensional direction and sp 2 Bonds and / or sp 3 It contains bonded Si atoms and has a thickness of 4 nm to 50 nm.
[0043] Such a silicon sheet 210 is formed by stacking and agglomerating silicon sheets, and has a thickness of several tens to several hundreds of nm. The silicon sheet 210 preferably has a thickness in the range of 100 nm or more and 300 nm or less. If the thickness is within this range, the silicon sheets can remain flexible even after stacking. The silicon sheet 210 more preferably has a thickness in the range of 150 nm or more and 250 nm or less. If the thickness is within this range, the silicon sheets can remain flexible and not easily broken even after stacking.
[0044] The silicon sheet 210 may preferably contain single-layer silicene or multiple silicene. This results in a laminate of silicon sheets having the above-mentioned thickness, and is expected to have a high specific capacitance. Note that the silicon sheet 210 may be substituted with functional groups such as hydroxyl groups, carboxyl groups, and carbonyl groups, or hydrogen atoms, in addition to silicon.
[0045] The content of the silicon sheet 210 in the composite 200 is preferably in the range of 35 wt% to 55 wt%. Within this range, a large specific capacity of silicon can be achieved. The content of the silicon sheet 210 is more preferably in the range of 40 wt% to 50 wt%. Note that although "wt%" is used in this specification, "mass%" may also be used.
[0046] Graphene sheet 220 is sp 2The graphene nanosheets are composed of carbon atoms bonded together, have a sheet-like shape with a hexagonal lattice structure, and are intended to be stacks (aggregates) of graphene nanosheets that constitute graphite. Note that the graphene sheet 220 may have functional groups such as hydroxyl groups, carboxy groups, and carbonyl groups in addition to carbon atoms.
[0047] Graphene sheet 220 is formed by stacking and aggregating graphene nanosheets having a thickness in the range of 0.3 nm to 10 nm, and has a thickness of several tens of nm to several hundreds of nm.
[0048] The graphene sheet 220 preferably has a thickness in the range of 30 nm to 150 nm. This range is advantageous for forming a three-dimensional space without losing the properties of the graphene nanosheet. The graphene sheet 220 more preferably has a thickness in the range of 50 nm to 120 nm. In this range, the graphene sheet 220 has excellent flexibility and can occlude a larger number of Li ions, so that a lithium ion secondary battery with a long life and high capacity can be provided.
[0049] It is preferable that the silicon sheet 210 and the graphene sheet 220 each satisfy the above-mentioned range, but more preferably, the thickness of the silicon sheet 210 is thinner than that of the graphene sheet 220. This allows the silicon sheet 120 to have flexibility as a whole and absorb more Li ions without breaking. In this specification, the thickness of each sheet is the average thickness of 20 sheets in an image observed by a transmission electron microscope.
[0050] The content of the graphene sheet 220 in the composite 200 is preferably in the range of 40 wt % to 60 wt %. Within this range, the above-mentioned silicon sheet 210 can be sandwiched. The content of the graphene sheet 220 is more preferably in the range of 45 wt % to 55 wt %.
[0051] The carbon material 230 is preferably amorphous carbon. In the composite 200, the carbon material 230 interposed between the silicon sheet 210 and the graphene sheet 220 and / or contained in the carbon-containing layer suppresses volume expansion due to insertion and desorption of Li ions when used as a negative electrode material for a lithium ion secondary battery, thereby improving cycle characteristics.
[0052] The carbon material 230 may further contain nitrogen. This allows a lithium ion secondary battery with a long life and high capacity to be provided. The nitrogen in the carbon material 230 may constitute pyridine-type nitrogen. If the nitrogen is pyridine-type nitrogen, it can function as a carrier or donor, and the conductivity of the carbon material 230 can be improved. The carbon material 230 may further contain oxygen.
[0053] The composite 200 constituting the flake silicon negative electrode material of the present invention is characterized in that the peak intensity corresponding to carbon is significantly large in the XPS spectrum measured by X-ray photoelectron spectroscopy (XPS). This means that the carbon content is significantly high with respect to the contents of silicon (Si), carbon (C), nitrogen (N), and oxygen (O) in the composite 200. As a result, a large specific capacity of silicon can be achieved in the flake silicon negative electrode material of the present invention.
[0054] In addition, the composite 200 constituting the flake silicon negative electrode material of the present invention has a Raman spectrum measured by Raman spectroscopy. D C for peak G The peak intensity is significantly larger than that of the C D C for peak GThe peak intensity ratio is 1.2 or more, preferably 1.3 or more, more preferably 1.4 or more, and even more preferably 1.5 or more. Satisfying such an intensity ratio means that the degree of graphitization of carbon in the composite is high. This is expected to increase the speed of electrochemical reactions and the amount of Li ion absorption, especially under conditions of high current density, and is advantageous as a negative electrode material.
[0055] (Embodiment 3) In the third embodiment, the use of the flake silicon negative electrode material of the present invention described in the second embodiment will be described.
[0056] The flake silicon negative electrode material of the present invention can be suitably used as a negative electrode material for lithium ion secondary batteries. Hereinafter, a lithium ion secondary battery using the flake silicon negative electrode material of the present invention will be described. FIG. 3 is a diagram illustrating a lithium ion secondary battery of the present invention.
[0057] The lithium ion secondary battery 300 of the present invention includes at least a positive electrode 310, a negative electrode 320, and an electrolyte 330. In FIG.
[0058] The positive electrode 310 is typically LiMO 2 (M is at least one element selected from the group consisting of Ni, Co, Mn, Fe, Ti, Zr, Al, Mg, Cr, and V) is known, but materials for positive electrodes used in existing lithium ion secondary batteries are applicable. The negative electrode 320 is made of the flake silicon negative electrode material of the present invention described in the second embodiment (FIG. 2).
[0059] The electrolyte 330 is not particularly limited as long as it is an existing electrolyte used in lithium ion secondary batteries. For example, LiClO 4 , LiPF 6 , LiBF 4 , LiPOF2 , LiAsF 6 , LiCF 3 SO 3 , LiCF 3 CF 2 SO 3 , LiC(CF 3 SO 2 ) 3 , LiN(CF 3 SO 2 ) 2 , LiN(CF 3 CF 2 SO 2 ) 2 , LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ) and LiN(CF 3 CF 2 CO) 2 The present invention contains at least one material selected from the group consisting of LiPF 6 is preferred because of its high electrical conductivity.
[0060] The lithium ion secondary battery 300 further includes a separator 340 between the positive electrode 310 and the negative electrode 320 to separate the positive electrode 310 and the negative electrode 320 .
[0061] The material of separator 340 is, for example, a material selected from a group consisting of fluorine-based polymers, polyethers such as polyethylene oxide and polypropylene oxide, polyolefins such as polyethylene and polypropylene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polymethyl acrylate, polyvinyl alcohol, polymethacrylonitrile, polyvinyl acetate, polyvinylpyrrolidone, polyethyleneimine, polybutadiene, polystyrene, polyisoprene, polyurethane-based polymers and derivatives thereof, cellulose, paper, and nonwoven fabric.
[0062] In the lithium ion secondary battery 300, the above-mentioned positive electrode 310, negative electrode 320, electrolyte 330, and separator 340 are housed in a cell 350. In addition, the positive electrode 310 and the negative electrode 320 may each have an existing current collector.
[0063] Such a lithium ion secondary battery 300 may be a chip type, coin type, button type, molded type, pouch type, laminate type, cylindrical type, square type, or other type of capacitor, and may further be used in a module in which multiple of these are connected together.
[0064] In this way, the lithium ion secondary battery of the present invention uses the flaky silicon negative electrode material of the present invention, so that the volume expansion caused by the insertion and desorption of Li ions into and from the negative electrode is suppressed, and high cycle characteristics can be achieved. In addition, the negative electrode using the flaky silicon negative electrode material of the present invention is highly flexible and can follow the volume change caused by the absorption and release of Li ions. As a result, the lithium ion secondary battery can have a long life.
[0065] In addition, since the flake silicon anode material of the present invention is agglomerated with high density silicon sheets, it is possible to provide a lithium secondary ion battery with a large capacity. Such a lithium ion secondary battery of the present invention can be used in portable electronic devices such as notebook computers and mobile phones.
[0066] The present invention will now be described in detail with reference to specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES
[0067] [Intermediate structure] CaSi placed on an alumina boat 2 (1.0 g) was placed in a tube furnace and CO was introduced at a flow rate of 0.2 L / min. 2 By supplying CaSi 2 CO 2 (Step S110 in FIG. 1). Table 1 shows the temperature conditions and reaction times used in this example. In addition, Fig. 4 shows the raw material CaSi 2 , and an SEM image of the intermediate structure obtained under the conditions of Example 6 shown in Table 1. A field emission scanning electron microscope (JSM-6500F, manufactured by JEOL Ltd.) was used for SEM observation. The same applies to the SEM images described later.
[0068] [Table 1]
[0069] Figure 4(a) and Figure 4(b) show the raw material CaSi 2 This figure shows SEM images (low and high magnification images) of CaSi 2 It can be seen that the SiO2 has a schist structure in which Ca layers and Si layers are stacked. 4(c) and 4(d) are SEM images (low and high magnification images) of the intermediate structure of Example 6. 2 and CO 2 When reacting with CaCO 3 is generated, and CaCO 3 It can be seen that a structure in which
[0070] [Silicone sheet] The intermediate structures obtained under the conditions of Examples 1 to 7 above were pickled with hydrochloric acid, washed with water, and dried at 40° C. for 10 minutes (Step S120 in FIG. 1). 5A and 5B show SEM images of samples obtained using the intermediate structures of Examples 4 to 7. FIG.
[0071] 5A is a diagram showing SEM images of samples obtained using the intermediate structures of Examples 4 and 5. The upper part of the figure is the sample of Example 4, and the lower part is the sample of Example 5, which are, from the left, a low-magnification image, a medium-magnification image, and a high-magnification image, respectively. 5B is a diagram showing SEM images of samples obtained using the intermediate structures of Examples 6 and 7. The upper row in the figure is the sample of Example 6, and the lower row is the sample of Example 7, which are, from the left, a low-magnification image, a medium-magnification image, and a high-magnification image, respectively.
[0072] From the SEM image shown in FIG. 5A, in both the samples of Example 4 and Example 5, CaCO 3 It was suggested that the Si layers were removed, but in the sample of Example 4, the inclusion (residual) of substances thought to be impurities was observed, making it difficult to clearly distinguish the individual Si layers. In the sample of Example 5, substances thought to be impurities were also observed, but the discernment of the Si layers was improved compared to the sample of Example 4, suggesting that the amount was negligible. From these results, it was found that in the manufacturing method of the present invention, the reaction temperature for obtaining the intermediate structure is preferably more than 800°C, and more preferably 850°C or higher.
[0073] In addition, from the SEM image shown in FIG. 5B, in both the samples of Example 6 and Example 7, CaCO 3 It was suggested that the Si layer was removed, but partial aggregation of the Si layer was observed in the sample of Example 7. From this result, it was found that in the manufacturing method of the present invention, the reaction temperature for obtaining the intermediate structure is desirably set to less than 950°C. On the other hand, in the sample of Example 6, the individual Si layers could be clearly distinguished, and no partial aggregation of the Si layers was observed, confirming that a silicon sheet composed of several Si layers was obtained in good condition.
[0074] Although not shown, the SEM images of the samples obtained using the intermediate structures of Examples 1 to 3 were similar to that of the sample of Example 4 (see FIG. 5A), and in particular, the samples of Examples 1 and 2 were found to have a large amount of mixed (residual) substances that seemed to be impurities. These results suggest that in the manufacturing method of the present invention, the reaction time for obtaining the intermediate structure is preferably more than 5 hours. In addition, when the reaction temperature is 750°C (the same as the highest temperature among the temperature conditions described in Non-Patent Document 1), the amount of CaSi 2 and CO 2 It was found that the reaction with did not proceed sufficiently, and many impurities were mixed in (residual) in the intermediate structure.
[0075] [Flake silicon anode material] Using the samples (silicon sheets) of Examples 4 to 7, flake silicon negative electrode materials were prepared. Specifically, each silicon sheet was added to an aqueous solution (10 mL) of the graphene oxide sheet and mixed to obtain a mixture (step S130 in FIG. 1). Here, the mixing ratio of each silicon sheet to the graphene oxide sheet was 50:50 in mass ratio. Next, the obtained mixture was slowly added to an aqueous chitosan solution, mixed, and then centrifuged and dried to obtain a precursor (step S140 in FIG. 1). Next, the obtained precursor was heated to 800° C. at a heating rate of 5° C. / min in an argon atmosphere and baked for 3 hours (step S150 in FIG. 1). Note that the graphene oxide sheet used was synthesized by the same method as described in the examples of Patent Document 1.
[0076] FIG. 6 shows SEM images of the sample (silicon sheet) of Example 6 before being subjected to the above steps, and the obtained product. 6(a) and 6(b) are SEM images (low and high magnification images) of the silicon sheet of Example 6. 6(c) and 6(d) are SEM images (low and high magnification images) of the product obtained using the silicon sheet of Example 6.
[0077] Comparing Figures 6(a) and (b) with Figures 6(c) and (d), it was found that by mixing a silicon sheet with a graphene oxide sheet in a dispersion medium, and then mixing this mixture with an aqueous solution of chitosan, a cationic polymer, and baking it, a structure was obtained in which the Si layer that constitutes the silicon sheet is covered (encapsulated) with a layer containing carbon (C) atoms.
[0078] Fig. 7 shows an SEM image of the product obtained using the silicon sheet of Example 6, and the results of element mapping analysis using the SEM image. Using the SEM image shown in the upper left of Fig. 7, element maps (concentration distributions) for carbon (C) and silicon (Si) shown in the upper right and lower left of Fig. 7 were obtained, respectively, and these were superimposed to produce the map (overlap) shown in the lower right of Fig. 7.
[0079] These results indicate that the obtained product has silicon uniformly distributed throughout the structure and is covered with graphene and carbon derived from the cationic polymer, confirming that the product is the desired flake silicon anode material.
[0080] FIG. 8 shows the results of structural analysis by X-ray diffraction (XRD, Rigaku Corporation, SmartLab, Cu-Kα radiation of λ=1.5418 Å). 8(a) to 8(d) are the analytical results for Example 6. FIG. 8(a) shows the raw material CaSi 2 FIG. 8(b) is an XRD pattern of the intermediate structure, FIG. 8(c) is an XRD pattern of the silicon sheet, and FIG. 8(d) is an XRD pattern of the flake silicon negative electrode material.
[0081] The XRD pattern in Fig. 8(a) shows the CaSi 2 The diffraction pattern was highly consistent with that of the data of No. 01-075-2192. These peaks were due to the CaSi 2 This indicates the presence of polycrystalline bodies, i.e., a flake-like Si layer.
[0082] In the XRD pattern of Figure 8(b), CaCO 3 A characteristic peak is seen at CaSi 2 Ca layer (calcium atom) and CO 2 The reaction with CaCO 3 This indicates that a
[0083] According to the XRD pattern of FIG. 8(c), in the silicon sheet obtained by pickling the intermediate structure with the pickling solution, CaCO 3 It can be seen that most of the intermediate products such as the above have been effectively removed, but it is suggested that very small amounts of impurities remain.
[0084] On the other hand, according to the XRD pattern in Figure 8(d), the impurity peaks have almost disappeared and a peak indicating the presence of amorphous carbon has appeared, which confirms that the desired flake silicon negative electrode material has been obtained, as in the results of the element mapping analysis described above.
[0085] Although not shown, XRD analysis was also performed on samples (silicon sheets) obtained using the intermediate structures of Examples 4, 5, and 7. The XRD patterns were similar to the diffraction pattern of the silicon sheet of Example 6 shown in FIG. 8(c).
[0086] FIG. 9 shows the results of analysis by Raman spectroscopy (Raman plus, manufactured by Nanophoton Corporation). 9(a) and 9(b) are Raman spectra of the silicon sheet of Example 6 and the flake-shaped silicon negative electrode material of Example 6, respectively.
[0087] In the Raman spectrum of Figure 9(a), the wave number is 520 cm -1 A single peak due to Si was clearly seen near the
[0088] In contrast, in the Raman spectrum of FIG. 9(b), in addition to the Si peak mentioned above, there is a peak at wavenumber 1594 cm -1 and 1357 cm -1 , C G Peak and C D A peak was observed. D C for peak G The peak intensity ratio was calculated to be about 1.58, indicating that the degree of graphitization of carbon in the flake silicon negative electrode material of Example 6 was high.
[0089] On the other hand, although not shown, the Raman spectrum of the material described in Patent Document 1 shows a Si peak and a C peak at the same wave numbers as those mentioned above. G Peak and C D A peak was observed, but C D C for peak G The intensity ratio of the peaks was less than 1.
[0090] FIG. 10 shows the results of analysis by X-ray photoelectron spectroscopy (XPS, ULVAC-PHI, PHI Quantera SXM). The lower part of FIG. 10 is an XPS spectrum of the silicon sheet of Example 6 (denoted as 2D-Si), and the upper part of FIG. 10 is an XPS spectrum of the flake silicon negative electrode material of Example 6 (denoted as 2D-Si@C).
[0091] From the XPS spectrum in the lower part of Figure 10, oxygen (O) and silicon (Si) were mainly detected in the silicon sheet of Example 6, and the peak derived from oxygen was particularly prominent, suggesting that the silicon sheet used in the present invention has low stability and is easily oxidized. In contrast to the relatively abundant oxygen atoms present on the surface of the silicon sheet, the presence of carbon (C) was found to be almost negligible.
[0092] In contrast, the XPS spectrum in the upper part of Figure 10 confirmed that the main constituent elements of the flake silicon anode material of Example 6 were carbon (C), oxygen (O), and silicon (Si). In particular, the peaks derived from carbon were prominent, and as explained with reference to Figure 6, it was found that the silicon layer constituting the silicon sheet was a structure covered (encapsulated) with a carbon-containing layer. In addition, the presence of nitrogen (N), which is thought to be derived from chitosan used as the cationic polymer, was also confirmed, and it was expected that the conductivity of the material would be improved by doping nitrogen atoms into the matrix composed of carbon atoms, thereby improving the electrochemical performance of the entire anode material.
[0093] Although not shown, the XPS spectrum of the material described in Patent Document 1 confirmed that the main constituent elements were carbon (C), oxygen (O), and silicon (Si), and also confirmed the presence of nitrogen (N). However, unlike the flake silicon negative electrode material of Example 6 described above, the intensities of the carbon-derived peaks and the oxygen-derived peaks were approximately the same.
[0094] FIG. 11 shows the results of analysis of the specific surface area and pore size distribution by nitrogen adsorption / desorption method (Quantachrome autosorb iQ, adsorption temperature 77 K). 11(a) to 11(c) are the analytical results for Example 6. FIG. 11(a) shows the results of the analysis of the raw material CaSi 2 FIG. 11(b) is a graph showing the nitrogen adsorption / desorption isotherm of the flaky silicon negative electrode material, and FIG. 11(c) is a graph showing the pore size distribution of the flaky silicon negative electrode material.
[0095] From the nitrogen adsorption / desorption isotherm in Fig. 11(a), the raw material CaSi 2 The specific surface area of is about 20m 2 Although not shown, the nitrogen adsorption / desorption isotherm of the intermediate structure of Example 6 shows that the specific surface area is 1.7 m 2 / g, and CaCO 3 However, the subsequent pickling resulted in the formation of a structure in which CaCO 3 By removing the impurities and other impurities, pores with a size distribution of about 1 nm to 5 nm are generated, and these voids become paths for the penetration of electrolyte and the transport of ions, ensuring the reactivity of the anode material. Furthermore, in the product obtained by mixing with graphene oxide sheets and cationic polymers and calcining the precursor, the specific surface area value was further decreased due to the coating and encapsulation of the Si layer by the carbon-containing layer described above (Figure 11(b)), but the tap density was increased. This suggests that while the energy density of the anode material increases, a considerable number of pores are retained, promoting the diffusion of the electrolyte, and a wide pore size distribution ranging from 1 nm to 20 nm was obtained (Figure 11(c)).
[0096] [Analysis of electrochemical properties] Next, CR2032 coin-type battery cells were fabricated using the flake silicon negative electrode materials of Examples 4 to 7, and the electrochemical properties were analyzed.
[0097] Specifically, each flake silicon negative electrode material, carbon black as a conductive assistant, and polyvinylidene difluoride (PVDF) as a binder were mixed in N-methylpyrrolidone (NMP) at a mass ratio of 7:2:1 to prepare an electrode slurry. The electrode slurry was applied to a circular copper foil with a diameter of 15 mm, and dried at 60°C for 10 hours in a vacuum atmosphere. This resulted in the construction of a negative electrode in which the copper foil functions as a current collector. The amount of the above material (active material) contained in the negative electrode was 0.8 mg / cm. 2 ~1.0mg / cm 2 Li foil was used as the positive electrode (counter electrode).
[0098] A polypropylene (PP) membrane (Celgard 2400) was placed between these electrodes as a porous separator in a stainless steel cell, and 1M LiPF in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (1:1, v / v) was used as the electrolyte. 6 The battery cell was assembled in a glove box filled with Ar gas.
[0099] Electrochemical measurements of the battery cell were performed using a VMP3 electrochemical station (Biologic). Cyclic voltammetry (CV) measurements, cycle characteristics, rate characteristics, and electrochemical impedance (EIS) measurements were performed at room temperature. CV measurements were performed at a sweep rate of 0.1 mV / s. Cycle characteristics and rate characteristics were measured at various current densities in the voltage range of 0.005 V to 2.0 V vs. Li / Li. + The EIS measurements were performed with an AC amplitude of 10 mV and a frequency range of 100 mHz to 200 kHz.
[0100] The analysis results obtained for the battery cell produced using the flake silicon negative electrode material of Example 6 (hereinafter referred to as the battery of Example 6) will be described below. Among the analysis results obtained from the battery cells fabricated using the flake silicon anode materials of Examples 4 to 7, the most excellent battery performance was obtained when the flake silicon anode material of Example 6 was used. From this, in the manufacturing method of the present invention, it is considered that the CaSi 2 and CO 2 Reaction conditions (temperature, time, CO 2 It was suggested that by appropriately adjusting the amount of the catalyst (e.g., the amount of catalyst supplied), the product obtained in the subsequent steps can exhibit superior properties as a negative electrode material.
[0101] FIG. 12 is a diagram showing a current-potential curve (cyclic voltammogram) of the battery of Example 6.
[0102] As shown in Figure 12, as the voltage decreases, continuous bonding between Li ions and Si atoms occurs, resulting in a broad peak around 1.0 V. This broadening of the peaks can be attributed to the formation of an SEI layer, i.e., a side reaction occurring between the electrolyte and the active material. Meanwhile, as the voltage decreases to 0.05 V, a reduction reaction gradually progresses, and a typical corresponding alloying reaction occurs. The two peaks seen at approximately 0.33 V and 0.5 V are due to the Li ions being converted into the above-mentioned alloy phase (Li x The reason is that the electrolyte is released from the silicon anode material (0≦x≦4.4). The CV profiles after that show a slight change (increase) after the first cycle, but they match well, suggesting that the electrode using the flake silicon anode material of Example 6 releases electrolyte quickly and has excellent electrochemical reversibility.
[0103] FIG. 13 shows the charge / discharge profiles of the battery of Example 6 for the first and second cycles shown in FIG.
[0104] As shown in Fig. 13, it can be seen that the decomposition of the electrolyte begins at about 1.0 V, leading to the formation of the above-mentioned SEI layer. The plateau shape observed around 0.5 V during the subsequent delithiation process matches well with the characteristic peak of the CV profile described with reference to Fig. 12.
[0105] The battery of Example 6 showed specific capacities of 1810 mAh / g and 2750 mAh / g, and the initial coulombic efficiency was calculated to be 66%, which is higher than the reported value (about 30%) for a typical Si electrode. In addition, the coulombic efficiency at the second cycle was significantly improved to 87%, suggesting that the reaction at the electrode using the flake silicon anode material of Example 6 proceeded reversibly.
[0106] FIG. 14 is a graph showing the rate characteristics of the battery of Example 6.
[0107] The battery of Example 6 showed a high specific capacity of about 2750 mAh / g at a current density of 0.1 C (where 1 C = 1000 mA / g). When the current density was increased to 3 C (30 times that of 0.1 C), the specific capacity showed a tendency to decrease. Then, when the current density was decreased to 0.3 C, the specific capacity was almost completely restored.
[0108] FIG. 15 is a diagram showing the Nyquist plot of the battery of Example 6.
[0109] As shown in FIG. 15, the Nyquist plot of the battery of Example 6 (before activation) showed an incomplete semicircular shape in the high frequency region, suggesting the presence of charge transfer resistance at the interface between the electrolyte and the active material (electrode). In contrast, the Nyquist plot after activation showed a smaller semicircular shape compared to the state before activation, suggesting that the above-mentioned charge transfer resistance was reduced and the electrochemical reaction was promoted. In addition, the equivalent series resistance before and after activation was calculated to be 117Ω and 35Ω, respectively, suggesting that the SEI layer was thinned by activation and the charge transfer at the electrode-electrolyte interface was improved. This is thought to be due to the presence of a carbon-containing layer contained in the electrode material (i.e., the flake silicon negative electrode material), which is advantageous for improving electrochemical performance.
[0110] FIG. 16 is a graph showing the cycle characteristics (@0.5C) of the battery of Example 6.
[0111] As shown in Figure 16, the specific capacity tends to gradually decrease with increasing cycles, but after 300 cycles the specific capacity remains at 300 mAh / g, exceeding the values reported for electrodes using conventional Si powder or amorphous Si. In addition, the coulombic efficiency showed a significant increase from about 66% in the first cycle to 99.9% after 300 cycles.
[0112] For further analysis, reaction kinetics was analyzed by varying the sweep rate in the CV measurement. The results obtained with the battery of Example 6 will now be described with reference to FIGS.
[0113] FIG. 17 shows current-potential curves obtained at sweep rates of 0.2 mV / s to 1.0 mV / s.
[0114] Generally, the relationship between peak current (i) and sweep rate (v) follows the following power law: i=av b (In the above formula, a and b are constants.) Here, b=0.5 suggests that the electrochemical behavior is dominated mainly by solid-state processes, whereas b=1.0 indicates that the capacity is mainly influenced by surface-controlled reactions. For the electrode prepared in this example, the value of b in the above formula was determined to be 0.55 based on the linear relationship between log(i) and log(v) shown in FIG. 18. This indicates that the Li absorption process in the negative electrode of the battery of Example 6 is mainly influenced by solid diffusion.
[0115] Also, the capacitive contribution (k 1 v) and the diffusion-controlled contribution (k 2 v 1 / 2 ) can be calculated individually using the following formula: i=k 1 v+k 2 v 1 / 2 (In the above formula, k 1 and k 2 is a constant. where k 1 and k 2 By calculating the value of , the ratio of the capacitive contribution to the diffusion control contribution can be obtained.
[0116] FIG. 19 is a diagram showing the results of calculating the ratio for each sweep rate (0.2 mV / s to 1.0 mV / s).
[0117] 19, the capacitive contribution increases as the sweep rate increases (speeds up), reaching 56% when the sweep rate is 1.0 mV / s. These results suggest that the use of a flake silicon negative electrode material produced using a silicon sheet obtained by the manufacturing method of the present invention is advantageous in the absorption and release of Li ions in the negative electrode of a lithium ion secondary battery. [Industrial Applicability]
[0118] The flake silicon anode material of the present invention is 2 Since the flake silicon anode material is produced using a silicon sheet obtained by a gas phase reaction using, the environmental impact during production is small. In addition, the method for producing the flake silicon anode material of the present invention can obtain the desired material efficiently and reproducibly in a relatively short time while avoiding the complication of the production process, and is therefore suitable for practical use and can be easily scaled up for mass production. [Explanation of symbols]
[0119] 200 Complex 210 Silicone Sheet 220 Graphene Sheet 230 Carbon Materials 300 Lithium-ion secondary battery 310 Positive electrode 320 Negative electrode 330 Electrolyte 340 Separator 350 cells
Claims
1. Calcium silicate (CaSi 2 ) under a temperature condition of more than 800°C and less than 950°C. 2 ) to obtain an intermediate structure; pickling the intermediate structure with an acid pickling solution to obtain a silicon sheet; mixing the silicon sheet and the graphene oxide sheet in a dispersion medium to obtain a mixture; mixing said mixture with an aqueous solution of a cationic polymer to obtain a precursor; calcining the precursor; The method for producing a flake silicon negative electrode material includes the steps of:
2. Obtaining the intermediate structure comprises: 2 Under temperature conditions of 860°C to 940°C, 2 The method according to claim 1 , wherein the reactant is a carboxylic acid or a carboxylic acid.
3. Obtaining the intermediate structure comprises: 2 Under temperature conditions of 875°C to 925°C, 2 The method according to claim 2, wherein the reactant is a carboxylic acid or a carboxylic acid.
4. Obtaining the intermediate structure comprises: 2 CO 2 The method according to any one of claims 1 to 3, wherein the reaction is carried out for more than 5 hours and not more than 15 hours.
5. Obtaining the intermediate structure comprises: 2 In a reactor containing CO 2 At a flow rate of 0.15 L / min to 0.3 L / min, CaSi 2 CO 2 The method according to any one of claims 1 to 3, wherein the compound is reacted with
6. The method according to any one of claims 1 to 3, wherein the pickling solution is an aqueous solution of an acid selected from the group consisting of sulfuric acid, hydrochloric acid and nitric acid.
7. The method according to any one of claims 1 to 3, wherein obtaining the mixture comprises mixing the silicon sheet and the graphene oxide sheet in a mass ratio of 65:35 to 75:
25.
8. The method according to any one of claims 1 to 3, wherein the cationic polymer is at least one selected from the group consisting of polyethyleneimine (PEI), polyvinylamine, polyallylamine, protamine, polylysine, polyornithine, polyarginine, chitosan, and polyvinyl alcohol.
9. The method according to any one of claims 1 to 3, wherein the calcination of the precursor is carried out at a temperature in the range of 600°C to 1000°C.
10. The method according to any one of claims 1 to 3, wherein obtaining the mixture comprises mixing the silicon sheet and the graphene oxide sheet under pressure.
Citation Information
Patent Citations
Carbon-coated two-dimensional silicon as well as preparation method and application thereof
CN111162266A
Preparation method and application of two-dimensional silicon nano material
CN111960422A
Anode electrode material, manufacturing method thereof, and lithium ion secondary battery using the same
JP2021166163A